2016
DOI: 10.1021/acs.jpcc.6b02083
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension of the Liquid–Vapor Interface of the Lennard-Jones Fluids from the Ising Model

Abstract: The surface tension of the Lennard-Jones fluids is described on the basis of the information about Ising model. We use the global isomorphism approach developed earlier for the bulk properties. It is shown that in broad interval of phase coexistence from triple point T tr to 0.9 T c the surface tension for Lennard-Jones fluids like noble gases can be reproduced on the basis of the information on the Ising model with mean deviation less than 3% (except for neon). In a 2D case, we use the Onsager exact solution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…In [18] it was shown that the phenomenological expression (25) is in agreement with the basic Trietzenberg -Zwanzig formula for the surface tension [48]:…”
Section: Effective Width Of Interfacementioning
confidence: 58%
See 4 more Smart Citations
“…In [18] it was shown that the phenomenological expression (25) is in agreement with the basic Trietzenberg -Zwanzig formula for the surface tension [48]:…”
Section: Effective Width Of Interfacementioning
confidence: 58%
“…These results encourage us to apply the global isomorphism relations to the surface tension. Earlier [18] it was shown how to use the results for the surface tension of the Ising model in order to get the surface tension of the molecular fluids in a wide temperature region.…”
Section: Global Isomorphism and The Zeno-linementioning
confidence: 99%
See 3 more Smart Citations